AGN accretion and black hole growth across compact and extended galaxy evolution phases. Issue 4 (1st August 2022) - Aird, James; Coil, Alison L; Kocevski, Dale D
ABSTRACT: The extent of black hole growth during different galaxy evolution phases and the connection between galaxy compactness and active galactic nucleus (AGN) activity remain poorly understood. We use Hubble Space Telescope imaging of the CANDELS fields to identify star-forming and quiescent galaxies at z = 0.5–3 in both compact and extended phases and use Chandra X-ray imaging to measure the distribution of AGN accretion rates and track black hole growth within these galaxies. We show that accounting for the impact of AGN light changes ∼20 per cent of the X-ray sources from compact to extended galaxy classifications. We find that ∼10–25 per cent of compact star-forming galaxies host an AGN, a mild enhancement (by a factor ∼2) compared to extended star-forming galaxies or compact quiescent galaxies of equivalent stellar mass and redshift. However, AGNs are not ubiquitous in compact star-forming galaxies and this is not the evolutionary phase, given its relatively short time-scale, where the bulk of black hole mass growth takes place. Conversely, we measure the highest AGN fractions (∼10–30 per cent) within the relatively rare population of extended quiescent galaxies. For massive galaxies that quench at early cosmic epochs, substantial black hole growth in this extended phase is crucial to produce the elevated black hole mass-to-galaxy stellar mass scaling relation observed for quiescent galaxies at z ∼ 0. We also show that AGN fraction increases with compactness in star-forming galaxies and decreases in quiescent galaxies within both the compact and extended subpopulations, demonstrating that AGN activity depends closely on the structural properties of galaxies.